2002
DOI: 10.1103/physrevb.65.224112
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the phase stability ofTiO2

Abstract: First-principles calculations of the crystal structures, bulk moduli, and relative stabilities of seven known and hypothetical TiO 2 polymorphs ͑anatase, rutile, columbite, baddeleyite, cotunnite, pyrite, and fluorite structures͒ have been carried out with the all-electron linear combination of atomic orbitals ͑LCAO͒ and pseudopotential planewave ͑PW͒ methods. The anatase versus rutile relative phase stability at 0 K and zero pressure has been investigated using high-quality basis sets and carefully controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
306
3
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(372 citation statements)
references
References 75 publications
57
306
3
6
Order By: Relevance
“…The rutile phase was chosen for the simulation since it is the most common natural form of TiO2. 42 As stated before, to the K point for ML MoS2. This is because using a bigger supercell in the DFT simulations results in the corresponding brillouin zone being smaller and, hence, the K point folds into the Γ point.…”
mentioning
confidence: 90%
“…The rutile phase was chosen for the simulation since it is the most common natural form of TiO2. 42 As stated before, to the K point for ML MoS2. This is because using a bigger supercell in the DFT simulations results in the corresponding brillouin zone being smaller and, hence, the K point folds into the Γ point.…”
mentioning
confidence: 90%
“…The titanium and oxygen ions are described using triple valence all-electron basis sets contracted as 86-411G** and 8-411G**, respectively. These basis sets were developed in previous studies of the bulk and surfaces of titania in which a systematic hierarchy of all-electron basis sets was used to quantify the effects of using a finite basis set 34,35 . The C and H atoms of the benzoate are described using basis sets of a similar quality, namely 6311G* and 821G*, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Anatase: Anatase TiO 2 also has a tetragonal structure but the distortion of the TiO 6 octahedron is slightly larger for the anatase phase [28,33], as depicted in Figure 1. Muscat et al [37] found that the anatase phase is more stable than the rutile at 0 K, but the energy difference between these two phases is small (∼2 to 10 kJ/mol). The anatase structure is preferred over other polymorphs for solar cell applications because of its higher electron mobility, low dielectric constant and lower density [23].…”
Section: Chemical Structure Of Tiomentioning
confidence: 99%